MO511BASELINE CHARACTERISTICS OF A NON-DIABETIC CKD COHORT IN A US CLAIMS DATABASE. (29th May 2021) - Wanner, Christoph; Schuchhardt, Johannes; Bauer, Chris; Lindemann, Stefanie; Brinker, Meike; Kong, Sheldon; Kleinjung, Frank; Horvat-Broecker, Andrea; Vaitsiakhovich, Tatsiana
Abstract: Background and Aims: Chronic kidney disease (CKD) is a major global health problem, affecting an estimated 850 million people worldwide. Non-diabetic CKD accounts for up to 70% of the CKD burden, which includes morbidity and mortality due to CKD progression to kidney failure and due to cardiovascular disease. This analysis uses real-world evidence to provide insights into the baseline clinical characteristics of individuals with non-diabetic CKD treated in routine clinical practice. Method: The Optum Clinformatics Data Mart was used to identify individuals with non-diabetic CKD (enrolled in the database between January 1, 2008 and December 31, 2018), based on common diagnosis, procedure and laboratory codes. To be eligible for inclusion, individuals were required to have CKD stage 3 or 4, as identified by estimated glomerular filtration rate (eGFR) 15–59 ml/min/1.73 m 2 and/or by an International Classification of Diseases (ICD) code, and confirmed by a second eGFR value or ICD code 90–365 days apart (index date). Individuals had to be ≥18 years old at index and have 365 days of continuous insurance coverage prior to the index event (baseline period). Those with diabetes mellitus, CKD stage 5 or end-stage kidney disease prior to the index date, or who experienced kidney failure (acute or unspecified), kidney transplant or dialysis at baseline, were excluded from the analysis. Patient demographics, clinical characteristics, comorbidities and medications were assessed at baseline. Results: Of the 64 million individuals in the Optum Clinformatics Data Mart during the analysed time period, 504, 924 satisfied the selection criteria. Median (interquartile range) age was 75 (68–81) years, 60% were female, 63% were white and 10% were black. The proportions of individuals with CKD stage 3 and 4 at index were 95% and 5%, respectively. At baseline, eGFR values were available for 62% of individuals; median (interquartile range) eGFR was 53 (47–57) ml/min/1.73 m 2 . A urine albumin-to-creatinine ratio was recorded in 6% of individuals, of whom 73%, 21% and 6% had normal-to-mildly increased (<30 mg/g), moderately increased (≥30 to ≤300 mg/g) and severely increased (>300 mg/g) albuminuria, respectively. The most common baseline comorbidities were hypertension (85% of individuals), hyperlipidaemia (68%), hypothyroidism (26%), anaemia (25%), pulmonary disease (24%) and coronary artery disease (24%). Heart failure, atrial fibrillation and peripheral artery disease were recorded in 16%, 15% and 14% of individuals, respectively. The most frequently used medication classes at baseline were statins (47% of individuals), beta blockers (44%), nonsteroidal anti-inflammatory drugs (36%) and angiotensin-converting enzyme inhibitors (34%). Angiotensin receptor blockers and mineralocorticoid receptor antagonists were used by 21% and 4% of individuals, respectively. The speciality of the diagnosing provider was reported on 26% of claims for the index event, the most common being family or internal medicine, followed by nephrology. Conclusion: This analysis contributes to the characterisation of a real-world population with non-diabetic CKD treated in routine clinical practice in the US. A large cohort of individuals with moderate-to-severe CKD was identified. The majority were elderly with multiple serious cardiovascular and pulmonary comorbidities and frequent use of nonsteroidal anti-inflammatory drugs. Overall, the analysis highlights the urgent need for improving early diagnosis, prevention and effective treatment of CKD.